2021
DOI: 10.1136/rmdopen-2020-001549
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of acute respiratory syndrome coronavirus 2 infection: a systematic literature review to inform EULAR points to consider

Abstract: BackgroundThe SARS-CoV-2 pandemic is a global health problem. Beside the specific pathogenic effect of SARS-CoV-2, incompletely understood deleterious and aberrant host immune responses play critical roles in severe disease. Our objective was to summarise the available information on the pathophysiology of COVID-19.MethodsTwo reviewers independently identified eligible studies according to the following PICO framework: P (population): patients with SARS-CoV-2 infection; I (intervention): any intervention/no in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 103 publications
0
12
0
2
Order By: Relevance
“…Severe COVID-19 is characterised by an excessive host immune response with overproduction of proinflammatory cytokines such as tumour necrosis factor (TNF), interleukin (IL)-6, growth factors such as granulocyte-macrophage colony-stimulating factor, and chemokines such as IL-8, a response known as cytokine storm ( figure 1 ). 2 , 3 Some proinflammatory cytokines induced in COVID-19 are therapeutic targets in the treatment of patients affected by immune-mediated inflammatory diseases. 4 Such cytokine inhibitors are widely used in the treatment of inflammatory arthritis, psoriasis, inflammatory bowel disease, and connective tissue disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Severe COVID-19 is characterised by an excessive host immune response with overproduction of proinflammatory cytokines such as tumour necrosis factor (TNF), interleukin (IL)-6, growth factors such as granulocyte-macrophage colony-stimulating factor, and chemokines such as IL-8, a response known as cytokine storm ( figure 1 ). 2 , 3 Some proinflammatory cytokines induced in COVID-19 are therapeutic targets in the treatment of patients affected by immune-mediated inflammatory diseases. 4 Such cytokine inhibitors are widely used in the treatment of inflammatory arthritis, psoriasis, inflammatory bowel disease, and connective tissue disorders.…”
Section: Introductionmentioning
confidence: 99%
“…It is of note that only one of the IgM+ participants received a positive RT-PCR for SARS-CoV-2 (on D1), and RP-PCR testing was negative for other coronaviruses. No IgM+ individuals who initially tested positive only for IgM ever developed documented IgG antibodies (per the Wytcote test) during the course of the study, potentially suggesting that the IgM results that were obtained were false positives [ 24 , 25 ]. It is possible that IgG antibodies developed but remained at undetectable levels or that they developed outside of the study period.…”
Section: Discussionmentioning
confidence: 99%
“…1.5.2 | Overproduction of pro-inflammatory cytokines, increased neutrophil-lymphocyte ratio and monocytosis Five studies assessing the cytokine release in COVID-19 reported increase of IL-1α, IL-1β, IL-1Ra, IL-6, IL-8, IL-10, IL-17, IL-18, tumour necrosis factor-α (TNF-α), IFN-α 2, IFN-γ, granulocyte colony-stimulating factor (G-CSF). 44 Some are produced by neutrophils and IL-8, IL-17 and TNF-α promote or are chemotactic for neutrophils. [45][46][47] High-serum IL-6, IL-8 and TNF-α levels at the time of hospitalization were strong and independent predictors of patient mortality.…”
Section: A Pathogenic Auto-inflammatory Feedback Loop?mentioning
confidence: 99%